Raman study of Ming porcelain dark spots: Probing Mn‐rich spinels. (18th February 2019) - Pinto, Ariane; Sciau, Philippe; Zhu, Tiequan; Zhao, Bing; Groenen, Jesse
Abstract: We report on the analysis of dendritic crystals present in the dark spot areas of blue‐and‐white Ming porcelains. Using Raman spectroscopy and scanning electron microscopy equipped with energy dispersive spectrometer, we were able to evidence Mn‐rich spinels. Small Mn‐based spinel crystals being highly sensitive to laser‐induced heating, we identified proper working conditions, avoiding excessive heating and damage. Local temperatures during Raman measurements were deduced from Stokes/anti‐Stokes intensity ratios. By analysing the behaviour of the A1g mode of Mn‐rich spinels, we were able to identify phases ranging from jacobsite‐like to hausmannite‐like compounds. Polarized Raman scattering was shown to provide a convenient means of discriminating between these two types of phases, as they display different symmetries. Inhomogeneities within the dendritic network, as evidenced by micro‐Raman measurements, highlight its gradual formation during the cooling phase of firing, depending of Fe 3+ and Mn 3+ availability. The presence of Mn‐based spinels is consistent with the use of a local Chinese Mn‐rich cobalt ore during the middle Ming Dynasty. Abstract : Dendritic crystals present in the dark spot areas of blue‐and‐white Ming porcelains were analysed. Using Raman spectroscopy and scanning electron microscopy equipped with energy dispersive spectrometer, we were able to evidence Mn‐rich spinels. Small Mn‐based spinel crystals being highly sensitive to laser‐induced heating, we identified proper working conditions, avoiding excessive heating and damage. Local temperatures during Raman measurements were deduced from Stokes/anti‐Stokes intensity ratios. Analysing the behaviour of the A1g mode of Mn‐rich spinels, we were able to identify phases ranging from jacobsite‐like to hausmannite‐like compounds. Polarized Raman scattering was shown to provide a convenient means of discriminating between these two types of phases, as they display different symmetries.